Kultus Kiai: Sketsa Tradisi Pesantren - Huda, M. Syamsul (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2011)
Study on kiai is a crucial and interesting discussion among Indonesian Muslim community. This article tries to find roots of problem on the emmergence of cult tradition towards kiai, mainly in pesantren community. The study uses field observation method, in-depth interview, and interpretation of the results. The research formulates cult tradition towards kiai within historical study, model and method of cult transformation, power and kiai?s authority, and the roots of cult among santris? community. The study finds that cult tradition towards kiai has emmerged from kiai?s personal power due to his knowledge charisma and his personality as well as institutional charisma as a result of intense and continous sociological relationship with other institutions.